Meningkatkan Kemampuan Computational Thinking Siswa Sekolah Dasar Menggunakan Lembar Aktivitas Unplugged Coding dalam Pembelajaran Matematika - Marito, Winanda; Riani, Nova (Indo-MathEdu Intellectuals Journal, 2025)
This research aims to improve the computational thinking (CT) skills of elementary school students through unplugged coding activity sheets in mathematics learning. The research uses a quantitative approach with a One Group Pretest-Posttest Design pre-experimental design. The subjects of the study are 25 fourth-grade students from Muhammadiyah 18 Medan, selected through purposive sampling. Data was collected using a CT ability test administered before and after the learning session. Data analysis was conducted using a paired sample t-test and N-Gain calculation. The research results show a significant increase in students' CT ability with an average score rising from 54.48 (pre-test) to 73.32 (post-test), a t-statistic value of -86.782, and a significance level of 0.000 (p < 0.05). The N-Gain value of 0.65 indicates the effectiveness of learning in the medium category. All CT indicators showed improvement, with generalization experiencing the highest increase (39.6%), followed by decomposition (39.3%), abstraction (38.9%), and algorithmic thinking (38.6%). However, the debugging and iteration indicators showed relatively lower increases of 28.7% and 23.6%, respectively. This research demonstrates that mathematics learning with unplugged coding activity sheets can be a solution to develop the CT abilities of primary school students with limited technological devices.